Ventricular segmentation and modeling using topological watershed transformation and harmonic state model. Issue 2 (13th October 2022) - Mahmoudi, Ramzi
Abstract: This paper proposes an adapted ventricular segmentation method based on topological watershed transform. Segmentation will allow spatio‐temporal modeling of trajectories of the different points belonging to the borders of the ventricle using a harmonic motion model that is able to describe such motion over the entire cardiac cycle. In addition, extraction of the adopted canonical state vector and the corresponding state equations guarantees an optimal efficacy and a gradual transition from order n to order n  + 1. To validate the proposed approach, an intern‐image base was used. Our results show a promising ability to discern whether subjects are healthy or pathological with an 80% success rate.